The Impact of Epigenetic Signatures on Amniotic Fluid Stem Cell Fate - Daniela Di Tizio; Alessandra Di Serafino; Prabin Upadhyaya; Luca Sorino; Liborio Stuppia; Ivana Antonucci (Stem Cells International)
Epigenetic modifications play a significant role in determining the fate of stem cells and in directing the differentiation into multiple lineages. Current evidence indicates that mechanisms involved in chromatin regulation are essential for maintaining stable cell identities. There is a tight correlation among DNA methylation, histone modifications, and small noncoding RNAs during the epigenetic control of stem cells’ differentiation; however, to date, the precise mechanism is still not clear. In this context, amniotic fluid stem cells (AFSCs) represent an interesting model due to their unique features and the possible advantages of their use in regenerative medicine. Recent studies have elucidated epigenetic profiles involved in AFSCs’ lineage commitment and differentiation. In order to use these cells effectively for therapeutic purposes, it is necessary to understand the basis of multiple-lineage potential and elaborate in detail how cell fate decisions are made and memorized. The present review summarizes the most recent findings on epigenetic mechanisms of AFSCs with a focus on DNA methylation, histone modifications, and microRNAs (miRNAs) and addresses how their unique signatures contribute to lineage-specific differentiation.